TRADISI MEMUTRU PADA UPACARA NGABEN DI DESA DARMASABA KECAMATAN ABIANSEMAL KABUPATEN BADUNG (Perspektif Pendidikan Agama Hindu) - I Made Rai Budayasa; I Nengah Sumantra; I Gede Garbha Putra (Upadhyaya : Jurnal Penelitian Pendidikan, 2023)
The Memutru tradition is one of the traditions in Darmasaba Traditional Village which is carried out on Ngaben ceremony. The problems that will be discussed such as: (1) How the traditional Memutru procession on Ngaben ceremony in Darmasaba Village?, (2) What is the function of the Memutru tradition on Ngaben ceremony in Darmasaba Village?, (3) How the value of internalizing the value of Hindu religious education contained therein. in the tradition of memutru on Ngaben ceremony in Darmasaba Village?. This study aims (1) to explain the process of implementing Memutru tradition on Ngaben ceremony in Darmasaba Village, (2) to describe the function of Memutru tradition on Ngaben ceremony, in Darmasaba Village (3) to analyze the internalization of the value of Hindu religious education contained in the Memutru tradition procession on Ngaben ceremony in the village of Darmasaba. The theories used to analyze the problem as follows: religious theory, functional structural theory, and behaviour theory. In this study, observation, interviews, literature and documentation used in collecting the data. The data were analyzed using qualitative descriptive analysis methods, data presentation, and drawing conclusions. Based on the analysis of the data, the results obtained are (1) The procession of the Memutru tradition on Ngaben ceremony begins with determining the “dewasa ayu” and preparing the infrastructure. Furthermore, the traditional Memutru procession is carried out on Ngaben ceremony. (2) The function of the Memutru tradition on Ngaben ceremony in Darmasaba Village, namely the religious function in strengthening sradha and devotional service, the Hindu religious education function, the purification function, glorification, preservation, the function of preserving the culture of Balinese genius local wisdom. (3) to internalizing the value of Hindu religious education in the tradition of Memutru on Ngaben ceremony in the village of Darmasaba, namely the internalization of educational values, namely, divine theology, social ethics, ethics of love, Yadnya, aesthetics, the highest value of prema/happiness